Development level of hosting areas and the impact of refugees on natives' labor market outcomes - Doğu Tan Aracı; Murat Demirci; Murat G. Kirdar (Koç University-TÜSIAD Economic Research Forum (ERF), 2021)
We examine how the impact of refugees on natives' labor market outcomes varies by the development level of hosting areas, which has important implications for the optimal allocation of refugees across regions and countries. For this purpose, in the context of the largest refugee group in the world in a single country, Syrian refugees in Turkey, we exploit the significant variation in the development level across regions of Turkey, several of which host a substantial number of refugees. We find that the impact of refugees on natives' labor market outcomes becomes significantly less adverse as regional development level rises. For instance, the negative effects of the refugee shock on employment and labor force participation of women observed at the mean level of development vanish at high levels of development. Moreover, while the impact of the refugees on employment of men is negative for the least developed regions, it is positive for highly developed regions. Our findings imply that developed regions and countries are in a better position in terms of protecting their local population from the adverse effects of refugees in the labor market.
Keywords: J61; O15; F22; R23; R58; 330; refugees; optimal refugee allocation; labor market impact; development level; employment and wages of men and women